The current status of human-elephant conflict in Kenya - Kiiru, Winnie (Pachyderm, 1995)
Summarises the present human-elephant conflict situation in Kenya. The estimated population of 24,000 animals is much less that two decades earlier, but the interactions with the expanding human population, particularly that which is agriculturally based have far greater economic and social ramifications.